Dynamic Behavior of Gas Nano-sized Bubbles in Liquid Phase of the Metal being Electrodeposited - О.B. Girin; I.М. Kuzyayev (Журнал нано- та електронної фізики)
The paper deals with the experimental results which confirm the occurrence of foam on the crests of waves of metals being electrodeposited in the course of their wavelike flow under action of the external force of insignificant value directed parallel to the crystallization front. The mechanism of foam formation on the crests of waves of metals being electrodeposited, conditioned by the dynamic behavior of gas nano-sized bubbles in the liquid phase of the metal being electrodeposited, is offered. The paper also presents the mathematical models for analysis of the dynamic behavior of gas nano- and micro-sized bubbles in the Newtonian and power-law liquids. Results of calculations on obtained mathematical models with the use of MathCAD package are given.